The Implementation of Prediction Strategy to Improve Student’s Reading Comprehension - Utama, Ade Putra; Ilma, Ridha; Husnaini (IKIP Siliwangi, 2025)
The purpose of this study was to investigate the effects of the Prediction Strategy on the reading comprehension of 40 students at one of Tahfizh Islamic Boarding School in Palembang. Using a nonequivalent group pretest-posttest design, the study used a quasi-experimental design. The Prediction Strategy was taught to the experimental group, and the lecture method was taught to the control group. Multiple-choice questions from pretests and posttests were used to gather the data. The results showed that after learning the Prediction Strategy, the experimental group's reading comprehension greatly increased. The experimental group's mean score skyrocketed from 71.25 to 83.00, whereas the control group's score grew from 75.38 to 80.12. The experimental group's improvement was statistically significant, according to the paired sample t-test (p-value = 0.000). However, the independent sample t-test revealed no significant difference between the two groups' posttest results (p-value = 0.469). The findings demonstrated that the Prediction Strategy helped students. The results showed that the Prediction Strategy was helpful in improving students' reading comprehension skills. As an alternative to teaching reading comprehension, the Prediction Strategy is advised.